Genetic Diversity Hopea celebica an Indonesian endemic species by ISSR Marker - Mirza Arsiaty Arsyad; Siti Halimah Larekeng; I. Iswanto; Muhammad Restu; Yuni Fitri Cahyaningsih; Michely Jauwdy Stevic (Universitas Sembilanbelas November Kolaka, 2022)
Indonesia is a mega-diversity country with numerous endemic plants distributed throughout its regions. An Indonesias’ island with the unique and the highest endemic plant species due to being located in the Wallace area is Sulawesi Island. Hopea celebica, an endemic species to Sulawesi Island, is currently categorized as endangered by IUCN. Here, we selected the ISSR primers suitable for the genetic study of H. celebica from Luwu and Konawe provenances and investigated their genetic diversity. Ten ISSR primers were employed in primer screening, and fifty H. celebicaindividuals were genetically analyzed for their genetic diversity. The selected ISSR primers for genetic diversity analysis were UBC 810, UBC 813, UBC 814, UBC 820, UBC 822, UBC 823, and UBC 827. The evaluated H. celebica individuals have high genetic diversity, and this information will be beneficial for designing H. celebica breeding and conservation strategies